2018
DOI: 10.1111/jocs.13740
|View full text |Cite
|
Sign up to set email alerts
|

Evolving trends in aortic valve replacement: A statewide experience

Abstract: During the study period, SAVR volume gradually declined and TAVR volume dramatically increased. This was mostly due to a new group of patients with lower STS PROM who were designated as higher risk by a Heart Team due to characteristics not completely captured by the STS PROM score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 15 publications
3
28
0
2
Order By: Relevance
“…In comparison to earlier studies that demonstrated steady increase in SAVR volume after TAVR program initiation, our study identified an inflection point after the initial volume increase followed by decline in the volume back to approximately the baseline level. Similar observation has been made at a state‐level data in Michigan . Concurrently observed was a significant increase in TAVR volume performed on patients with nonhigh risk populations.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In comparison to earlier studies that demonstrated steady increase in SAVR volume after TAVR program initiation, our study identified an inflection point after the initial volume increase followed by decline in the volume back to approximately the baseline level. Similar observation has been made at a state‐level data in Michigan . Concurrently observed was a significant increase in TAVR volume performed on patients with nonhigh risk populations.…”
Section: Discussionsupporting
confidence: 82%
“…European experience that preceded the FDA approval in the U.S. provided initial insight into the ‘halo’ effect, in which 37% increase in SAVR volume was observed in a center that initiated TAVR programs, assumed to be due to increase in the overall referral volume via the multidisciplinary heart valve program. Subsequently, a similar phenomenon was observed in U.S. studies at an institutional, state‐wide, and national levels . This increase has been surmised to be due to the increase in overall AVR referral volume owing to the institution of TAVR programs.…”
Section: Discussionsupporting
confidence: 62%
“…However, between 50 and 70 years of age, patient preference is the dominant factor affecting the choice of a prosthesis. With rapid growth of transcatheter AVR (TAVR) over the past decade, the use of bAVR has had simultaneous increase in growth, with the thought that a valve‐in‐valve (V‐I‐V) TAVR could be performed when structural valve degeneration (SVD) of the bAVR occurs …”
Section: Introductionmentioning
confidence: 99%
“…In this edition of the Journal, Kim et al report the most recent trends in surgical (SAVR) and transcatheter (TAVR) aortic valve replacement from the Michigan Society of Thoracic and Cardiovascular Surgeons Quality Collaborative database from 2012 to 2017. They found that the total annual AVR volume increased by 40% (2086‐2920) with a 13.3% decrease in SAVR (1892‐1640) and a 560% increase in TAVR (194‐1280).…”
mentioning
confidence: 99%